Peran Orang Tua dalam Membentuk Karakter Islami Anak di Desa Kluwut Kecamatan Bulakamba - Ika Fatimatun Azizah; Hakimuddin Salim (Jayapangus Press, 2026)
The family, as the first educational environment for children, plays a crucial role in the formation of Islamic character. However, the high level of parental activity and work demands may reduce the intensity of their involvement in guiding and instilling Islamic values in their children. This study aims to provide an in-depth explanation of the role of parents in shaping children’s Islamic character in Kluwut Village, Bulakamba District, as well as to identify the challenges encountered in its implementation. This research employs a qualitative approach with a case study design, using observation, interviews, and documentation as data collection techniques. The findings reveal that parents hold a very significant role in shaping Islamic character, as reflected in their roles as educators, motivators, and role models. As educators, parents instill the values of tauhid, habituate religious practices, and foster moral conduct as well as social awareness. As motivators, they provide encouragement and appropriate appreciation to reinforce positive behavior. As role models, parents demonstrate Islamic values in their daily lives, serving as concrete examples for their children. The challenges faced include limited time due to work demands and the influence of digital technology. Nevertheless, parents continue to strive to perform their roles optimally by utilizing available time and implementing adaptive parenting strategies. These findings indicate that consistent and high-quality parental involvement is a key factor in the successful development of children’s Islamic character.